If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -8) + -1(-5x + 10) + 5(2 + -4x) + -3x = 10x + -7 Reorder the terms: 3(-8 + 2x) + -1(-5x + 10) + 5(2 + -4x) + -3x = 10x + -7 (-8 * 3 + 2x * 3) + -1(-5x + 10) + 5(2 + -4x) + -3x = 10x + -7 (-24 + 6x) + -1(-5x + 10) + 5(2 + -4x) + -3x = 10x + -7 Reorder the terms: -24 + 6x + -1(10 + -5x) + 5(2 + -4x) + -3x = 10x + -7 -24 + 6x + (10 * -1 + -5x * -1) + 5(2 + -4x) + -3x = 10x + -7 -24 + 6x + (-10 + 5x) + 5(2 + -4x) + -3x = 10x + -7 -24 + 6x + -10 + 5x + (2 * 5 + -4x * 5) + -3x = 10x + -7 -24 + 6x + -10 + 5x + (10 + -20x) + -3x = 10x + -7 Reorder the terms: -24 + -10 + 10 + 6x + 5x + -20x + -3x = 10x + -7 Combine like terms: -24 + -10 = -34 -34 + 10 + 6x + 5x + -20x + -3x = 10x + -7 Combine like terms: -34 + 10 = -24 -24 + 6x + 5x + -20x + -3x = 10x + -7 Combine like terms: 6x + 5x = 11x -24 + 11x + -20x + -3x = 10x + -7 Combine like terms: 11x + -20x = -9x -24 + -9x + -3x = 10x + -7 Combine like terms: -9x + -3x = -12x -24 + -12x = 10x + -7 Reorder the terms: -24 + -12x = -7 + 10x Solving -24 + -12x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -24 + -12x + -10x = -7 + 10x + -10x Combine like terms: -12x + -10x = -22x -24 + -22x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 -24 + -22x = -7 + 0 -24 + -22x = -7 Add '24' to each side of the equation. -24 + 24 + -22x = -7 + 24 Combine like terms: -24 + 24 = 0 0 + -22x = -7 + 24 -22x = -7 + 24 Combine like terms: -7 + 24 = 17 -22x = 17 Divide each side by '-22'. x = -0.7727272727 Simplifying x = -0.7727272727
| x^2-64x+620=0 | | 42x^2-5= | | 6/7(7y-14)=-9 | | 11x+67=5x+25 | | 501x-42y=3 | | x^2-6x+15=7 | | 6x-6y=48y | | x-45=x/4 | | 87x+12y=-14 | | 2(n-1)=2(3n-1) | | 6+4+x=9+1 | | -24-6x=-6(-2+3x) | | 4x(x)+20x+25=0 | | -3-5x=-2x-3(x+1) | | 3/7x-13=17 | | ln(x)-ln(3x)=3 | | 4x(x)+20x= | | 24x-60=60x-24 | | -7x-12=-2-6(1+x) | | 1/4(8x-20)=1/8(15x-6) | | 9(x+10)+4=-7(x-1)-3 | | -4(b-8)=32-4b | | 0.28=glox | | 0=380x-10500-x^2 | | 2y+3=8y-7 | | 9x+94=-7(x-1)-3 | | -6/5y-7=5 | | 5k-24=4(3k+8) | | 4x+6=x+1 | | 50x^3/10x | | x-3/2=-2 | | 5(x-8)+14=2(x+17)+9x |